Addition to the review of the genus Wroughtonia Cameron, 1899 (Hymenoptera, Braconidae, Helconinae) from Vietnam: Description of two new species - Oanh, Nguyen Thi; Long, Khuat Dang; Pham, Nhi Thi; Mai, Pham Quynh; Nghiep, Hoang Thi (Zootaxa, 2024)
In the present study, the genus Wroughtonia Cameron from Vietnam is revised with two new species described and illustrated, viz. Wroughtonia phiaoaca Long, sp. nov. and W. robustifemur Long, sp. nov.. Comparative morphological characters of the new Wroughtonia species are discussed. An in-country distribution map of the known Vietnamese species of Wroughtonia is also provided.